LO90: Trauma triage accuracy at a Canadian trauma centre. (15th May 2017) - Pace, J.; Tillmann, B.; Ball, I.; Leeper, R.; Parry, N.; Vogt, K.
Abstract : Introduction: Trauma teams have been shown to improve outcomes in severely injured patients. The criteria used to mobilize trauma teams is highly variable and debated. This study was undertaken to define the triage accuracy at our level 1 trauma centre and identify the criteria predictive of appropriate activations.Methods: A 3-month prospective observational study was performed and all patients presenting to the ER who received a trauma flag were identified. Patient demographics, vital signs, trauma team activation and criteria for activation were documented. Trauma activations were deemed appropriate if the patient met any of the following; airway intervention, needle/tube thoracostomy, resuscitative thoracotomy, ED blood product transfusion, invasive hemodynamic monitoring, central line insertion, emergent OR (<8 hours), admission to ICU, and death within 72 hours. Over and undertriage rates were calculated and a multivariate logistic regression was performed to identify activation criteria predictive of appropraite activations. The activation criteria were then modified and the prospective study was repeated to assess the impact on triage accuracy.Results: Between September to December 2015, 188 patients received a trauma flag. 137 patients met the activation criteria, however only 78 received a trauma team activation. 57% of patients who had TTA met the definition of appropriate activation, while 45% who met criteria for activation met the definition of appropriate. The rates of under and overtriage were 30.4% and 30.3%, respectively. Logistic regression revealed the following criteria to be predictive of appropriate activation; hypotension (OR 10.2 95% CI 2.3, 45.5), arrival by HEMS (OR 3.2, 95% CI 1.4, 7.6), pedestrian struck (OR 3.5, 95% CI 1.4, 8.5) and fall (OR 5.1, 95% CI 1.7, 15.1). Tachycardia (OR 1.1, 95% 0.3, 4.6) and high energy MVC (OR 1.4, 95% CI 0.7, 3.1) were not found to be predictive. The post-modification study occured between September to December 2016. Data analysis to assess the impact of criteria alteration are currently underway and will be presented at CAEP 2017.Conclusion: Triage accuracy for the mobilization of a multi-disciplinary trauma team is important, both to ensure optimal patient care as well as to reduce unnecessary resource strain. Our previous criteria lead to high rates of undertriage and subsequent modifications have been made. The impact of these changes will be ascertained and presented at CAEP 2017.